The impacts of marine heatwaves on ecosystems and fisheries in Aotearoa New Zealand - Katie M. Cook; Matthew R. Dunn; Erik Behrens; Matt H. Pinkerton; Cliff S. Law; Vonda J. Cummings (New Zealand Journal of Marine and Freshwater Research, 2025)
Marine heatwaves (MHWs) are increasing in frequency and intensity globally, yet the impacts of such extreme events are not well understood. We review the effects of MHWs on the fisheries and ecosystems of Aotearoa‐New Zealand (NZ), an island nation with over 15,000 km of coastline, and 4 million km 2 of exclusive economic zone, that supports diverse marine communities and valuable commercial and recreational fisheries. Using Aotearoa‐NZ and global literature, we discuss the potential effects of MHWs on the physical environment and on species, populations and ecosystems. We review recorded national impacts with a fisheries focus, and systematically assess MHW effects on 32 commercially or culturally important Aotearoa‐NZ wild‐caught fishery or aquaculture species, classifying their vulnerabilities. We found records of MHW‐induced ecosystem shifts, with macroalgae community change, and out‐of‐range occurrences of warm‐water species. Of the 32 species examined, national MHW impacts were documented for three species (green‐lipped mussel, snapper, and Chinook salmon). We highlight the paucity of information for life‐stage specific impacts, and indirect impacts such as changes in predator‐prey interactions and biogenic habitat distributions. Assessing MHW impacts through a fisheries lens highlights the need for enhanced interdisciplinary research and monitoring, to develop sustainable management strategies under environmental change.